SHASHI DESHPANDE IS A CONTEMPORARY INDIAN FEMINIST WRITER - FROM A FEMINIST PERSPECTIVE - Sharma, Narayani (ShodhKosh: Journal of Visual and Performing Arts, 2021)
Since the beginning of the world, there has been a struggle to liberate women from male oppression. In the past, the work of women writers has always been marginalized due to certain patriarchal ideas. Feminism is an expression of the unwillingness to mistreat a woman. In literature, it refers to a style that approaches a text according to the nature of the female experience. The differences that women have raised in their voices Legal, economic and social restrictions on women's basic rights can be seen throughout history.